Characterization of Bubble Pearls from a Mixture of Tapioca and Glucomannan - Rusdianto, Andrew Setiawan; Purnamasari, Devi Ashila; Herlina, Herlina (International Journal on Food, Agriculture and Natural Resources, 2024)
Boba is a drink originating from Taiwan that has become popular in the Indonesian beverage industry in recent years. This drink consists of a mixture of tea with fruit or milk flavors, with the addition of tapioca-based black chewy textured balls called bubble pearls/boba. Bubble pearls made from tapioca are known to have low nutrition and fiber, so it is necessary to improve their functional characteristics by utilizing local commodities, one of which is porang. Porang (Amorphophallus oncophyllus Prain) as one of the local commodities has the potential to improve the characteristics of bubble pearls. Glucomannan flour from porang tubers has high glucomannan content, quite high fiber content, and can form a gel. This study aims to determine the characteristics of bubble pearl products with the addition of glucomannan flour and to determine the optimum percentage of glucomannan flour and tapioca. The formulation of bubble pearls was carried out using the Simplex Lattice Design method and their physical, chemical, and hedonic characteristics were analyzed. The optimization parameters included water absorption capacity, gumminess level, and dietary fiber content. The optimum formula produced by the Simplex Lattice Design method is in formula 2, bubble pearls with the addition of 25% glucomannan flour which has the highest desirability value of 0.862. Formula 2 consists of a water absorption capacity of 37.08%, a gumminess level of 45.72 gf, and a dietary fiber content of 5.65%. The hedonic values are 5.73 for color (slightly like), 5.7 for aroma (slightly like), 4.8 for hardness (neutral), 4.73 for chewiness (neutral), 5.23 for taste (slightly like), and 5.4 overall (slightly like). Additionally, the water content is 59.97% and the ash content is 1.41%.